Thyroid‐associated orbitopathy is linked to gastrointestinal autoimmunity. (October 2014) - Ponto, K. A.; Schuppan, D.; Zwiener, I.; Binder, H.; Mirshahi, A.; Diana, T.; Pitz, S.; Pfeiffer, N.; Kahaly, G. J.
Summary Common autoimmune disorders tend to co‐exist in the same subjects and cluster in families. The objective of this study was to determine the prevalence of autoimmune co‐morbidity in patients with autoimmune thyroid disease (AITD) with and without thyroid‐associated orbitopathy (TAO). This was a cross‐sectional study conducted at an academic tertiary referral centre. Of 1310 patients with AITD [n = 777 or 59% with Graves' disease (GD) and n = 533, 41% with Hashimoto's thyroiditis (HT)] followed at a specialized joint thyroid–eye out‐patient clinic, 176 (13·4%) had an adult type of the autoimmune polyglandular syndrome, 129 (9·8%) type 1 diabetes, 111 (8·5%) coeliac disease, 60 (4·6%) type A autoimmune gastritis, 57 (4·4%) vitiligo and 25 (1·9%) Addison's disease. Coeliac disease and autoimmune gastritis were associated positively with GD [odds ratio (OR) = 2·18; P = 0·002 and OR = 6·52; P < 0·001], whereas type 1 diabetes, Addison's disease, autoimmune primary hypogonadism, alopecia areata, rheumatoid arthritis and Sjögren's syndrome were 'protective' for GD and thus linked to HT, OR = 0·49 (P < 0·001), 0·06 (P < 0·001), 0·25 (P < 0·001), 0·50 (P = 0·090) and 0·32 (P = 0·003), respectively. Of 610 (46·6%) AITD patients with TAO, 584 (95·7%) and 26 (4·3%) had GD and HT, respectively (P < 0·001). TAO was most prevalent in GD patients with coeliac disease (94%, OR = 1·87, P < 0·001). Multivariate analysis showed high OR for coeliac disease and autoimmune gastritis (3·4 and 4·03, both P < 0·001) pertaining to the association with TAO while type 1 diabetes, Addison's disease and alopecia areata were protective for TAO. In patients with TAO, coeliac disease is the most prevalent co‐morbid autoimmune condition and rates are increased compared to GD patients without TAO.